The Influence of AI Technology on Employee Engagement - Ryan Marshal Fauzy; Gurawan Dayona Ismail; Nunung Ayu Sofiati (Efi); Yoyo Sudaryo; Dadan Abdul Aziz Mubarok (Eduvest - Journal of Universal Studies, 2026)
This study aims to analyze the influence of the use of AI HR Chatbot, technology adaptation, and AI-based performance appraisal systems on employee engagement with internal communication effectiveness as an intervening variable among employees at Bank Banten Head Office. The research background is based on the phenomenon of decreased employee performance and the adaptation challenges to the digital transformation being carried out by the company. The use of Artificial Intelligence (AI) based technology in human resource management is expected to increase the effectiveness of internal communication, appraisal transparency, and employee involvement in the organization6. The research method used is a quantitative approach with data collection through questionnaires distributed to employees at Bank Banten Head Office. Data analysis was performed using path analysis technique to test the direct and indirect relationships between variables8. The results show that the use of AI HR Chatbot, technology adaptation, and AI-based performance appraisal systems have a positive and significant influence on employee engagement, both directly and through internal communication effectiveness as a mediating variable9. Internal communication effectiveness is proven to strengthen the relationship between AI-based technology and the level of employee involvement. The conclusion of this study confirms the importance of integrating AI technology into the human resource management system supported by effective internal communication to enhance emotional attachment, motivation, and employee performance. The practical implication of this research is the need for a human-centered digitalization strategy and transparent communication policies so that the implementation of AI in the workplace can run optimally.